2012
DOI: 10.1186/1475-2859-11-40
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the proline and nitric oxide synthetic pathway improves fermentation ability under multiple baking-associated stress conditions in industrial baker's yeast

Abstract: BackgroundDuring the bread-making process, industrial baker's yeast, mostly Saccharomyces cerevisiae, is exposed to baking-associated stresses, such as air-drying and freeze-thaw stress. These baking-associated stresses exert severe injury to yeast cells, mainly due to the generation of reactive oxygen species (ROS), leading to cell death and reduced fermentation ability. Thus, there is a great need for a baker's yeast strain with higher tolerance to baking-associated stresses. Recently, we revealed a novel an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…In the baking industry, further advances such as high fermentation ability, frozen tolerance and osmototolerance of baker's yeasts have been demanded in recent decades to adapt the changed conditions during the baking process (Sasano and others , 2013; Sun and others ; Lin and others ). One of the important technological goals is to develop baker's yeast strains (mostly Saccharomyces cerevisiae ) with high fermentation ability (Alves–Araújo and others ; Sasano and others ).…”
Section: Introductionmentioning
confidence: 99%
“…In the baking industry, further advances such as high fermentation ability, frozen tolerance and osmototolerance of baker's yeasts have been demanded in recent decades to adapt the changed conditions during the baking process (Sasano and others , 2013; Sun and others ; Lin and others ). One of the important technological goals is to develop baker's yeast strains (mostly Saccharomyces cerevisiae ) with high fermentation ability (Alves–Araújo and others ; Sasano and others ).…”
Section: Introductionmentioning
confidence: 99%
“…Because Mpr1 confers AZC resistance on various organisms, selectable marker systems using the MPR1 gene and AZC have been constructed for yeast and plant transformation (33)(34)(35). We recently showed that industrial yeast strains expressing the Mpr1 variant are more tolerant to oxidative stresses, such as ethanol, freezing, and desiccation, than those expressing WT-Mpr1 (29,36,37). Engineered Mpr1 might be useful in breeding oxidative stress-tolerant yeast strains with improved fermentation ability.…”
Section: Discussionmentioning
confidence: 99%
“…The proline catabolism by Saccharomyces cerevisiae also leads to flavour biosynthesis, the intermediary compound being glutamate, which is further degraded to aroma compounds [15].…”
Section: Amino Acids' First Specific Degradation Pathwaymentioning
confidence: 99%